Analisis Penanganan Pembiayaan Bermasalah pada Bank Syariah Indonesia KCP Sibuhuan - Askur Hamid Nasution (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research discusses the handling of problematic funding at Bank Syariah Indonesia KCP Sibuhuan. Based on observations in the field, many consumer financing problems, especially for certain products, arise due to various factors. The aim of this research is to find out the strategies used by Bank Syariah Indonesia KCP Sibuhuan in handling problematic financing for consumer products, as well as the factors that cause these problems and the steps that must be taken if these problems arise. Again. The research was conducted using a qualitative methodology, and the findings show that Bank Syariah Indonesia KCP Sibuhuan's approach to overcoming problematic financing in consumer financing products is to develop the company's human resources (HR), providing advice to clients via telephone and face-to-face conversations. visits, and perfecting the company website, all that remains is for the client to submit a Warning Letter (SP), chat with the client, develop a financing restructuring strategy, and finally implement the final handling strategy by selling the client's assets or collateral. Financial problems at Bank Syariah Indonesia KCP Sibuhuan are not caused by internal bank problems, but external factors such as customer lifestyle, layoffs, requests for other financing, unreliable customers, and work at bad companies. If an opportunity arises, problematic consumer goods are being refinanced at Bank Syariah Indonesia KCP Sibuhuan. This is done by assessing the money given, talking to all financial units, and avoiding problems with previous financing.